Analisis Kesulitan Pronunciation pada Siswa Kelas VIII SMPN 4 Mangarabombang - Uzlifatil Jannah Binti Samir; Kusmiyati Kusmiyati; Ariana Ariana (FKIP, Universitas Palangka Raya, 2026)
This study aims to analyze the types of pronunciation difficulties and the internal and external factors influencing the pronunciation abilities of eighth-grade students at SMPN Mangarabombang within the context of the KKN educational program. The ability to pronounce English words accurately is an essential component of language learning because it supports effective communication and improves students’ speaking confidence. This research employed a qualitative descriptive case study approach, using participatory observation and in-depth interviews with five students as the primary data collection techniques. The findings reveal that the major pronunciation difficulties stem from phonetic interference from Indonesian, particularly in producing unfamiliar English sounds and applying appropriate word stress, especially in number-related vocabulary. Internally, students tend to focus more on memorizing vocabulary meanings than practicing correct pronunciation, resulting in limited repetition and insufficient pronunciation practice. Externally, although students are passively exposed to English through songs and other media, the lack of interactive learning resources, limited classroom pronunciation activities, and minimal use of English during instruction further contribute to their pronunciation problems. These findings indicate that both linguistic and instructional factors play important roles in shaping students' pronunciation abilities. Therefore, teachers are encouraged to implement more communicative learning strategies, strengthen phoneme and word stress instruction, provide regular pronunciation practice, and utilize engaging learning media to create an interactive learning environment. Such efforts are expected to improve students’ pronunciation accuracy, confidence, and overall English-speaking competence.